ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA APBDESA (STUDI KASUS DESA BULAK KECAMATAN BENDO KABUPATEN MAGETAN) - Dizzy Asrinda Siswi Ramadhani; Nur Hisamuddin; Moch. Shulthoni (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2019)
The research was conducted to analyze financial ratios in order to assess the performance of village governments through village revenue and expenditure budgets for 2015, 2016, and 2017. The financial ratios used in the study were 5 namely independence ratio, harmony ratio, growth ratio, efficiency ratio, and effectiveness ratio. This research is quantitative descriptive. The research object is Bulak Village, Magetan Regency. The research was conducted using data from the village revenue and expenditure budget from 2015-2017. The results showed that the performance of the Bulak Village government from the aspect of independence and aspects of harmony was still very lacking. The growth rate of Desa Bulak is quite good, and the efficiency levels of 2015 and 2016 are inefficient, while 2017 is quite efficient, while the effectiveness of 2015, 2016 and 2017 is effective. Keywords: Expenditure Budget, Financial Ratio, Performance Measurement, Village Revenue (APBDes).